English Learning Materials for Restaurant Students at Apollonia Hotel School - Ariyanthi, Ketut Eni; Putra, I Nyoman Adi Jaya; Suarcaya, Putu (Journal of Education Reseach and Evaluation, 2020)
This study aims to develop learning materials in the form of books for restaurant students at Apollonia Hotel School Denpasar. The method of the current study is Design and Development. In developing the learning material, this study uses the DnD model by Richey and Klien. There were several processes carried out, namely identifying learning materials needed; developing learning materials in the form of books; and evaluating the results of material development. The results of the study found that there are eight types of material that need by restaurants students namely procedure of handling cleanliness, maintain kitchen and restaurant equipment, renewing local knowledge, provide a link between kitchen area and service area, provide gueridon service, provide silver service, provide food and beverage service, and provide room service. The results of expert tests showed the score of the learning material developed is 85 which belongs to good category.